Answer:
Explanation:
10). m(arc AB) = m(arc BC) = m(arc CA) [given in the picture]
m(arc AB) =
= 120°
Therefore, m(arc ACB) = m(arc AC) + m(arc BC)
= 120° + 120°
= 240°
11). m(arc CD) = 127° [Given]
m(arc AB) = 51° [Given]
m(arc AC) = m(arc BD) [Given]
m(arc CD) + m(arc BD) + m(arc AB) + m(arc AC) = 360°
127° + 2[m(arc BD)] + 51° = 360°
178° + 2[m(arc BD)] = 360°
2[m(arc BD)] = 360° - 178°
m(arc BD) = 91°
Since, m(arc CDB) = m(arc CD) + m(arc BD)
Therefore, m(arc CDB) = 127°+ 91°
= 218°
12). m(arc EH) + m(arc ED) + m(arc DH) = 360°
180° + 53° + m(arc DH) =360°
m(arc DH) = 360° - 233°
m(arc DH) = 127°